Ambient Air Quality and Meteorological Monitoring of Gaseous Pollutants in Urban Areas of Gwalior City India. Issue 3 (2nd July 2020) - Dandotiya, Banwari; Sharma, Harendra K.; Jadon, Nimisha
Abstract: This article reports on a study conducted to determine the concentration of SO2 and NO2 in various urban residential zones in an urban area of Gwalior City. The aim of this study was to examine the spatiotemporal variations of gaseous air pollutants at four sites in the Gwalior urban area. The concentrations of NO2 and SO2 were systematically monitored according to national ambient air quality guidelines provided by Central Pollution Control Board, India. Among the various finding, this article documents that concentrations of gaseous pollutants were most elevated in commercial and high traffic areas.